2018
DOI: 10.1111/pedi.12687
|View full text |Cite
|
Sign up to set email alerts
|

Transition to adult diabetes care in Germany-High risk for acute complications and declining metabolic control during the transition phase

Abstract: This phase of life bears a high risk for detrimental outcome in young adults with T1D. Structured transition programs with case management are therefore needed to improve the transition process and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 15 publications
0
15
1
9
Order By: Relevance
“…In adults, the median HbA 1c testing frequency was 8 (5; 9) times per 2 years, with 64% of the individuals being categorized as undergoing 'frequent' HbA 1c testing (at least seven HbA 1c measurements per 2 years) [16]. Transition from paediatric to adult care is a crucial time, however, and is often associated with deterioration of metabolic control [17][18][19]. In a T1DX survey of young adults aged 18 to <30 years who had already transitioned to adult care, 21% of the respondents reported a gap of >6 months between paediatric and adult diabetes care [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, the median HbA 1c testing frequency was 8 (5; 9) times per 2 years, with 64% of the individuals being categorized as undergoing 'frequent' HbA 1c testing (at least seven HbA 1c measurements per 2 years) [16]. Transition from paediatric to adult care is a crucial time, however, and is often associated with deterioration of metabolic control [17][18][19]. In a T1DX survey of young adults aged 18 to <30 years who had already transitioned to adult care, 21% of the respondents reported a gap of >6 months between paediatric and adult diabetes care [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a T1DX survey of young adults aged 18 to <30 years who had already transitioned to adult care, 21% of the respondents reported a gap of >6 months between paediatric and adult diabetes care [17]. A DPV study even indicated that 60% of individuals with type 1 diabetes transitioning from paediatric to adult care had a period of >1 year between the last paediatric care visit and the first adult care visit [18].…”
Section: Discussionmentioning
confidence: 99%
“…Individuell unterschiedlich terminiert steht dann die Transition von der pädiatrischen Diabetologie in die Erwachsenen-Diabetologie an. Oftmals ist in dieser Zeit der Verantwortungsverschiebung eine Reduktion der Therapieadhärenz und Sorgfalt mit weniger Glukosemessungen und einem Anstieg des HbA 1c -Werts zu beobachten [5].…”
Section: Introductionunclassified
“…The transfer from pediatric care to adult care carries a considerable health risk for youth with special health care needs (YSHCN [1][2][3]. This phase is associated with missed medical appointments [4,5], poor health outcomes [6] and lower overall quality of life [7,8]. Recommendations include structural changes in health care systems [9][10][11] as well as propositions on how to support patients while transferring [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%